Histological section of the head of an adult Pleuragramma antarcticum - Stefano Aicardi (12040249); Matteo Bozzo (12040216); Andrea Amaroli (12040217); Lorenzo Gallus (419689); Beatrice Risso (12040225); Erica Carlig (12040254); Davide Di Blasi (12040227); Marino Vacchi (12040229); Laura Ghigliotti (12040231); Sara Ferrando (514464) (2022)
Histological section of the anterior part of the head of adult Pleuragramma antarcticum . Azan trichrome. Complete scan of the section acquired at x100 magnification.